2015
DOI: 10.1016/j.aogh.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Review of Occupational Health and Safety Organization in Expanding Economies: The Case of Southern Africa

Abstract: The full adoption and success of OHS systems in Southern Africa remains constrained. Training and education in OHS, especially in occupational medicine, will enhance the development and maturation of occupational health in southern Africa. Capacitating primary health services with basic occupational health knowledge would be invaluable in bridging the current skills deficit. Introducing short courses and foundational tracks in occupational medicine for general medical practitioners would be invaluable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 0 publications
4
37
0
Order By: Relevance
“…Furthermore, according to the respondents the rate if accidents and mishaps had also decreased since the implementation of the occupational safety and health policies. This finding is again evident from the study made by Moyo et al [40], Ndejjo et al [50] and Siziya et al [60], where the researchers too indicated reduction in occupational hazards and accidents after the implementation of the OSH policies. Again, from the challenges and opportunities of OSH implementation, the most important challenge was financial and lack of resources.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…Furthermore, according to the respondents the rate if accidents and mishaps had also decreased since the implementation of the occupational safety and health policies. This finding is again evident from the study made by Moyo et al [40], Ndejjo et al [50] and Siziya et al [60], where the researchers too indicated reduction in occupational hazards and accidents after the implementation of the OSH policies. Again, from the challenges and opportunities of OSH implementation, the most important challenge was financial and lack of resources.…”
Section: Resultssupporting
confidence: 63%
“…Furthermore, respondents 3, 9, 11 and 17 also recommended leadership and management of employees also changed which had improved the workplace performance. With respect to the relevance of the responses, Moyo et al [40] and Puplampu et al [7] reported with similar findings. Again, European Agency for Safety and Health at Work [34] and World Health Organization [1] too supported the current findings where, implementation of OSH lowered occupational hazards and risks.…”
Section: Effect Of Coaching In Oshsupporting
confidence: 70%
See 3 more Smart Citations